2022
DOI: 10.1128/spectrum.00826-21
|View full text |Cite
|
Sign up to set email alerts
|

A Peptide from Budding Yeast GAPDH Serves as a Promising Antifungal against Cryptococcus neoformans

Abstract: Cryptococcus neoformans and Cryptococcus gattii can cause cryptococcosis, which has a high mortality rate. To treat the disease, amphotericin B and fluconazole are often used in clinic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 64 publications
0
11
0
Order By: Relevance
“…S4). Combining these observations of the cap59 Δ mutants and the fact that the dense network structure of polysaccharide capsule was severely damaged after treatment of SP1 ( 32 ), we postulated that SP1 destroyed the capsule to expose proteins or polysaccharide, and the interactions of these exposed substances might induce the flocculation of C. neoformans H99. When the flocs were treated with 3 mg/mL proteinase K, the cell aggregation caused by SP1 was dispersed ( Fig.…”
Section: Resultsmentioning
confidence: 83%
See 4 more Smart Citations
“…S4). Combining these observations of the cap59 Δ mutants and the fact that the dense network structure of polysaccharide capsule was severely damaged after treatment of SP1 ( 32 ), we postulated that SP1 destroyed the capsule to expose proteins or polysaccharide, and the interactions of these exposed substances might induce the flocculation of C. neoformans H99. When the flocs were treated with 3 mg/mL proteinase K, the cell aggregation caused by SP1 was dispersed ( Fig.…”
Section: Resultsmentioning
confidence: 83%
“…Previously, we reported that SP1 can specifically kill C. neoformans and Cryptococcus gatti ( 32 ). Scanning electronic microscopy showed that SP1 damaged the capsule of C. neoformans H99 ( 32 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations